Computational Modulation in Electronic Structures of Halide Perovskites via Element/Dopant/Phase - Choi, Jae Won (Langmuir : the ACS journal of surfaces and colloids, 2024)
This study employs computational chemistry to investigate the electronic properties of halide perovskite materials, focusing on structural frameworks, elemental composition, surface engineering, and defect engineering. The tetragonal phase generally exhibits higher band gaps than the cubic phase due to conduction band differences, with LiPbCl3 showing the greatest band gap difference. The ionic radius of the A element influences band gaps for both phases, with Cs having the highest impact. Surface engineering significantly affects the electronic properties, and surface direction and composition play vital roles in determining band gaps. Defect engineering induces semiconducting-to-metallic transitions, impacting band gaps. Understanding these core variables is crucial for tailoring the electronic properties of halide perovskites for photovoltaic and optoelectronic applications